Theoretical Relationship between the Confining Pressure and Poisson’s Ratio of Intact Rock - Lógó, Benedek A.; Vásárhelyi, Balázs (Periodica Polytechnica Civil Engineering, 2022)
The Poisson’s ratio of the intact rock material is one of the basic material constants for rock engineering calculations in and on rock environments. Recently, several relationships were developed to calculate of the Poisson’s ratio of the intact rock from different mechanical parameters (e.g., rigidity index, cohesion, internal friction angle). This value can be measured under standardized laboratory conditions using traditional uniaxial compressive test at zero confining pressure. Analyzing the laboratory tests carried out at different confining pressure, it was found that this material constant should be increasing as a function of confining pressure. This paper aims to present a theoretical relationship between Poisson’s ratio of intact rock and the confining pressure, using the Hoek-Brown failure criteria. It was assumed that the Poisson’s ratio is increasing linearly, and at the brittle-ductile transaction point, it is 0.5. The proposed relationship can be extended to rock mass, using the Geological Strength Index (GSI).